Tracing cyber attacks from the practical perspective. - Zhiqiang Gao (IEEE Communications magazine)
The integrity of the Internet is severely impaired by rampant denial of service and distributed DoS attacks. It is by no means trivial to devise a countermeasure to address these attacks because of their anonymous and distributed nature. This article presents a brief survey of the most promising recently proposed schemes for tracing cyber attacks: IP traceback. Since IP traceback technology is evolving rapidly, for the community to better comprehend and capture the properties of disparate traceback approaches, we first classify these schemes from multiple aspects. From the perspective of practicality and feasibility, we then analyze and explore the advantages and disadvantages of these schemes in depth so that shortcomings and possible enhancements of each scheme are highlighted. Finally, open problems and future work are discussed, and concluding remarks are drawn.